Light-Addressable Potentiometric Sensors in Microfluidics - Li, Xueliang; Liu, Shibin; Tan, Jie; Wu, Chunsheng (Frontiers in Bioengineering and Biotechnology, 2022)
The light-addressable potentiometric sensor (LAPS) is an electrochemical sensor based on the field-effect principle of semiconductors. It is able to sense the change of Nernst potential on the sensor surface, and the measuring area can be controlled by the illumination of a movable light. Due to the unique light-addressable ability of the LAPS, the chemical imaging system constructed with the LAPS can realize the two-dimensional image distribution detection of chemical/biomass. In this review, the advantages of the LAPS as a sensing unit of the microelectrochemical analysis system are summarized. Then, the most recent advances in the development of the LAPS analysis system are explained and discussed. In particular, this review focused on the research of ion diffusion, enzymatic reaction, microbial metabolism, and droplet microfluidics using the LAPS analysis system. Finally, the development trends and prospects of the LAPS analysis system are illustrated.